1997
DOI: 10.1080/026782997208820
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a lateral aromatic branch on the orientational ordering of laterally alkoxy substituted nematics

Abstract: Two new mesogenic series have been synthesized. They have the same main core which contains four aromatic rings, with two lateral substituents on the same side of one of the inner rings. One of the substituents is a 4-chlorobenzyloxy group and the second is an alkoxy chain. The positions of the lateral substituents are di erent in the two series. Despite the large aromatic branch, an enantiotropic nematic phase is obtained for most of the compounds. The orientational ordering behaviour of these new compounds h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…The two lateral chains were found to be folded back along the mesogenic core, involving a gaucheconformation for the ® rst segment. The molecular long axis of the core seemed not to be in¯uenced by the found that the para-axis of the lateral aromatic ring makes a non-negligible angle with respect to the core [1 ].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The two lateral chains were found to be folded back along the mesogenic core, involving a gaucheconformation for the ® rst segment. The molecular long axis of the core seemed not to be in¯uenced by the found that the para-axis of the lateral aromatic ring makes a non-negligible angle with respect to the core [1 ].…”
Section: Introductionmentioning
confidence: 95%
“…As a consequence, Our previous NMR studies have revealed that when an the mesogenic core needs to be su ciently long in order to preserve the liquid crystal properties [1]. compounds containing four aromatic rings in the main core and two lateral substituents on one of the inner rings, one alkoxy chain and a 4-chlorobenzyloxy branch; they exhibited the nematic phase [1 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As a consequence, in a homologous series, the conventional mesogens, alkyl or alkoxy chains are used melting temperatures can be adjusted by changing the as terminal fragments [1]. The chain conformation in number of carbons within the terminal and/or lateral the solid phase of these compounds is usually trans and chains without aOE ecting too much the nematic range the crystal cohesion which contributes to the value of [5][6][7]. the melting temperature is mainly due to core-core Nematogens containing the oxyethylene unit have two interactions.…”
Section: Introductionmentioning
confidence: 99%
“…4, the 1,3-dimethyluracil ring and the two phenyl rings (or biphenyl moiety) which is adjacent to the spacer appear at different positions depending on the number of carbons at the alkoxy spacer [34][35][36]. The models indicate that 1.3-dimethyluracil and biphenyl core groups take at different side where the number of carbons at spacer change from n = 6 to 10.…”
Section: Molecular Modelingmentioning
confidence: 99%